2000
DOI: 10.1001/jama.283.19.2579
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Quality

Abstract: Socioeconomic and racial/ethnic disparities in health care quality have been extensively documented. Recently, the elimination of disparities in health care has become the focus of a national initiative. Yet, there is little effort to monitor and address disparities in health care through organizational quality improvement. After reviewing literature on disparities in health care, we discuss the limitations in existing quality assessment for identifying and addressing these disparities. We propose 5 principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
231
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,008 publications
(249 citation statements)
references
References 87 publications
7
231
0
Order By: Relevance
“…26 Evidence suggests that interventions aimed all or in part at patients can be highly successful in improving BP control. 20,41 While quality improvement may lessen disparities in care, 42 our results suggest EMR reminders, a commonly employed quality improvement intervention, are unlikely to be sufficient to eliminate disparities in hypertension care and control. Thus, we conclude that a rising tide does not lift all boats equally, and that specifically targeted interventions must be used in future efforts to decrease disparities in the process and outcomes of hypertension care.…”
Section: Bp Control and Disparities Intervention -Kressin Et Almentioning
confidence: 73%
“…26 Evidence suggests that interventions aimed all or in part at patients can be highly successful in improving BP control. 20,41 While quality improvement may lessen disparities in care, 42 our results suggest EMR reminders, a commonly employed quality improvement intervention, are unlikely to be sufficient to eliminate disparities in hypertension care and control. Thus, we conclude that a rising tide does not lift all boats equally, and that specifically targeted interventions must be used in future efforts to decrease disparities in the process and outcomes of hypertension care.…”
Section: Bp Control and Disparities Intervention -Kressin Et Almentioning
confidence: 73%
“…The mechanisms underlying it, however, are not fully understood (Elo, 2009). Earlier research has suggested that one important cause of social inequality in health is differences in quality of health care (Beckfield et al, 2015;Fiscella et al, 2000). Quality of health care comprises both the effectiveness of and access to health care .…”
Section: Introductionmentioning
confidence: 99%
“…ad justed count lsoa = ad justed rate lsoa × population lsoa (1) The waiting times indicator was indirectly standardised in a similar manner at LSOA level but instead of standardising for age and sex this indicator was standardised for the specialty code of the treating consultant. This was done in order to risk-adjust waiting time for the specialty of the admission, on the basis of the value judgement that a difference in the patient's specialty of treatment may be a legitimate justification for a longer waiting time, but not a difference in their age or sex.…”
Section: Methodsmentioning
confidence: 99%